An Outbreak of Acute Chagas Disease Possibly Spread through Oral Transmission Involving Animal Reservoirs in Eastern Colombia (2024)
Chagas disease (CD) is a parasitic infection caused by the parasite Trypanosoma cruzi. Reports of CD cases associated with oral transmission have increased, particularly in Colombia, Brazil, and Venezuela. In this investigation, parasitological, serological, and molecular tests were conducted on samples obtained from humans, mammal reservoirs, and hosts involved in the assessment of a suspected oral transmission outbreak in Cubara, Boyaca, Colombia. Seropositivity was observed in 60% (3 of 5) of index patients and 6.4% (5 of 78) of close contacts. Trypanosoma cruzi DNA was detected by quantitative polymerase chain reaction in 100% of index cases, 6.4% (5 of 78) of close contacts, 60% (6 of 10) of canines, and 100% (5 of 5) of opossums. In all index cases, the TcI lineage was identified, along with two cases of mixed infection (TcI/TcII-TcVI). Hemoculture revealed a flagellate presence in 80% of opossums, whereas all triatomine bugs tested negative. Our findings suggest a potential oral transmission route through contamination with opossum secretions.